2021
DOI: 10.1016/s2589-7500(21)00118-7
|View full text |Cite
|
Sign up to set email alerts
|

The need for feminist intersectionality in digital health

Abstract: Digital health, including the use of mobile health apps, telemedicine, and data analytics to improve health systems, has surged during the COVID-19 pandemic. The social and economic fallout from COVID-19 has further exacerbated gender inequities, through increased domestic violence against women, soaring unemployment rates in women, and increased unpaid familial care taken up by women-all factors that can worsen women's health. Digital health can bolster gender equity through increased access to health care, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 54 publications
1
76
0
3
Order By: Relevance
“…To best meet the needs of older veterans, and older adults more generally, future research should utilize qualitative methods and co-design processes to ensure that interventions are solving mental health challenges in usable, meaningful, and engaging ways. Co-design can help address barriers that are specific to older adults (eg, [ 69 ]); ensure that the product is findable, accessible, usable, desirable, credible, useful, and valuable (eg, [ 70 ]); improve the overall quality of the product [ 71 ]; and promote equity and inclusion (eg, [ 72 , 73 ]). More research focused on effective dissemination and implementation strategies is also needed.…”
Section: Discussionmentioning
confidence: 99%
“…To best meet the needs of older veterans, and older adults more generally, future research should utilize qualitative methods and co-design processes to ensure that interventions are solving mental health challenges in usable, meaningful, and engaging ways. Co-design can help address barriers that are specific to older adults (eg, [ 69 ]); ensure that the product is findable, accessible, usable, desirable, credible, useful, and valuable (eg, [ 70 ]); improve the overall quality of the product [ 71 ]; and promote equity and inclusion (eg, [ 72 , 73 ]). More research focused on effective dissemination and implementation strategies is also needed.…”
Section: Discussionmentioning
confidence: 99%
“…Commentaries: Six (n = 6) included papers were commentaries (Banks et al, 2021; Das et al, 2021; Figueroa et al, 2021; Goodsmith et al, 2021; Hinton et al, 2021; Richey & Pointer, 2021) (see Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…A viewpoint paper (Figueroa et al, 2021) from the USA illustrated gender inequality issues in digital health at three levels: users, tools (i.e., mobile phone applications) and leadership.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, our previous review on conversational agents for physical activity identified only a handful of conversational agents for mobile delivery through apps and text messaging, and no Spanish conversational agents ( 15 ). Further, digital solutions are not often specifically designed for women ( 18 ), especially ethnic minority women, who generally have worse health outcomes than white women ( 19 ). Ethnic minority women are underrepresented in the design and testing of digital health tools ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, digital solutions are not often specifically designed for women ( 18 ), especially ethnic minority women, who generally have worse health outcomes than white women ( 19 ). Ethnic minority women are underrepresented in the design and testing of digital health tools ( 18 ). Because of this and the lack of adequate digital skills training, marginalized groups may underuse these interventions ( 20 ), even if health technologies target them.…”
Section: Introductionmentioning
confidence: 99%